1975
DOI: 10.1136/oem.32.3.203
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological study of occupational bladder tumours in the dye industry of Japan.

Abstract: This report studies 100 cases of occupational bladder cancer which were reported between 1949 and 1970 by large companies producing dye. It is estimated that in fact a great many more than 100 cases may have developed during the 56 years from 1914 to 1970, as this period corresponds with the beginning of dye production to the termination of benzidine and beta-naphthylamine manufacture in Japan. New cases of occupational bladder tumour should diminish significantly in the future in Japan on account of the prohi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…The study's cancer incidence rate could be the same, or shift to the left (smaller side) if these workers are taken into consideration 2 . This incidence rate is not significantly different from the statistical data of other Japanese dye‐plant workers 3 . The subjects are systematically followed up by our well‐established system as described in .…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…The study's cancer incidence rate could be the same, or shift to the left (smaller side) if these workers are taken into consideration 2 . This incidence rate is not significantly different from the statistical data of other Japanese dye‐plant workers 3 . The subjects are systematically followed up by our well‐established system as described in .…”
Section: Discussionmentioning
confidence: 82%
“…Ishizu studied 3310 workers who had been exposed to bladder cancer‐related chemicals and reported that the incidence and mortality for those workers were 4.4% and 0.82%, respectively 13 . In addition, Tsuchiya et al reported 100 bladder cancers out of 2524 exposed workers (3.96%) in Japan 3 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 The number of people who are at high risk for bladder cancer due to occupational exposure to aromatic amines (AA) amounts to more than 6000 in the United States,3 3000 in Japan (Ad hoc committee on industrial hygiene of the Japan Dyestuff Industry Association), and 2500 in China.4 Therefore, management of asymptomatic workers at high risk for bladder cancer is still important.…”
mentioning
confidence: 99%